A soft systems approach for innovation in the fruits and vegetables market in Uruguay - Berrutti, Marcela Marques; Pizzolon, Alejandro; Álvarez, Jorge Ariel (Sustainability in Debate, 2023)
"Systems thinking" approaches include some techniques and methods developed by social scientists to encourage debate, recognising that their practice is inevitably full of value and that research is a part of intervention. In general, systems theories explain the need to transcend disciplines to increase our understanding of a situation by considering different levels of impact, especially through visualisation tools. In a very complex environment such as the fruit and vegetable market in Uruguay, especially focusing on the roles of agents and the interactions between them, "soft systems methodologies"contributed to building a representation integrating different perspectives with consensual and conflicting aspects, delving into the particularities and opportunities for technological innovations and collaborative management for the fruit and vegetablechain, ending in important reflections on opportunities for positive change and the risks of marginalisation or social exclusion. Commercial channels for farm products and main agents Particularities of Uruguayan consumption Alternative channels, collaborative management and other innovations: for whom? It is considered that this approach contributes to building a holistic vision of the situation that will facilitate our understanding of the commercial circumstances in rural Uruguay (Checkland 1999). In particular, we discuss innovations promoted by the recent crisis linked to the start of the Covid-19 pandemic in 2020 and the challenges posed by climate change, questioning the proposal of generating " value added " with the idea of "integral valuation".